Impact on human health of particulate matter emitted from burnings in the Brazilian Amazon region Impactos na saúde humana de partículas emitidas por queimadas na Amazônia brasileira - Eliane Ignotti; Joaquim Gonçalves Valente; Karla Maria Longo; Saulo Ribeiro Freitas; Sandra de Souza Hacon; Paulo Artaxo Netto (Universidade de São Paulo, 2010)
OBJECTIVE: To analyze the impact on human health of exposure to particulate matter emitted from burnings in the Brazilian Amazon region. METHODS: This was an ecological study using an environmental exposure indicator presented as the percentage of annual hours (AH%) of PM2.5 above 80 μg/m3. The outcome variables were the rates of hospitalization due to respiratory disease among children, the elderly and the intermediate age group, and due to childbirth. Data were obtained from the National Space Research Institute and the Ministry of Health for all of the microregions of the Brazilian Amazon region, for the years 2004 and 2005. Multiple regression models for the outcome variables in relation to the predictive variable AH% of PM2.5 above 80 μg/m3 were analyzed. The Human Development Index (HDI) and mean number of complete blood counts per 100 inhabitants in the Brazilian Amazon region were the control variables in the regression analyses. RESULTS: The association of the exposure indicator (AH%) was higher for the elderly than for other age groups (β = 0.10). For each 1% increase in the exposure indicator there was an increase of 8% in child hospitalization, 10% in hospitalization of the elderly, and 5% for the intermediate age group, even after controlling for HDI and mean number of complete blood counts. No association was found between the AH% and hospitalization due to childbirth. CONCLUSIONS: The indicator of atmospheric pollution showed an association with occurrences of respiratory diseases in the Brazilian Amazon region, especially in the more vulnerable age groups. This indicator may be used to assess the effects of forest burning on human health. OBJETIVO: Analizar el impacto a la salud humana por la exposición al material particulado de las emisiones de incendios en el Amazonas brasilero. MÉTODOS: Estudio ecológico utilizando el indicador de exposición ambiental, presentado como porcentaje anual de horas (AH%) de PM2,5 encima de 80 µg/m³ y como resultado tasas de hospitalización por enfermedades respiratorias en niños, ancianos y grupos etarios intermediarios y tasas de hospitalización por parto. Los datos fueron obtenidos del Instituto Nacional de Pesquisas Espaciales y del Ministerio de la Salud de Brasil para todas las microrregiones del Amazonas Brasilero, en los años 2004 y 2005. Fueron analizados modelos de regresión múltiple de las variables de resultado con la variable predoctora AH% encima de 80 µg/m³ para PM2,5. El Índice de Desarrollo Humano (IDH) y el número promedio de hemogramas por 100 habitantes en la región del Amazonas Brasilero fueron variables de control en los análisis de regresión. RESULTADOS: Se observó mayor asociación del indicador de exposición (AH%) para los ancianos en comparación con otros grupos etarios (? = 0,10). Para cada punto porcentual de aumento en el indicador de exposición, hubo aumento de 10% en la tasa de hospitalización de ancianos, 8% en internaciones de niños, y 5% para el grupo etario intermedio, aún ajustando por IDH y número promedio de hemogramas. No fue encontrada asociación entre AH% y la tasa de hospitalización por parto. CONCLUSIONES: El indicador de polución atmosférica mostró asociación con la ocurrencia de enfermedades respiratorias, en especial en los grupos etarios más vulnerables del Amazona Brasilero, pudiendo ser utilizado en el abordaje de los efectos de incendios de las selvas en la salud humana. OBJETIVO: Analisar o impacto à saúde humana pela exposição ao material particulado das emissões de queimadas na Amazônia brasileira. MÉTODOS: Estudo ecológico utilizando o indicador de exposição ambiental apresentado como percentagem anual de horas (AH%) de PM2,5 acima de 80 μg/m³ e como desfecho taxas de hospitalização por doenças respiratórias em crianças, idosos e grupos etários intermediários e taxas de hospitalização por parto. Os dados foram obtidos do Instituto Nacional de Pesquisas Espaciais e do Ministério da Saúde para todas as microrregiões da Amazônia Brasileira, nos anos 2004 e 2005. Foram analisados modelos de regressão múltipla das variáveis de desfecho com a variável preditora AH% acima de 80 μg/m³ para PM2,5. O Índice de Desenvolvimento Humano (IDH) e o número médio de hemogramas por 100 habitantes na região da Amazônia brasileira foram variáveis de controle nas análises de regressão. RESULTADOS: Observou-se maior associação do indicador de exposição (AH%) para os idosos do que para outros grupos etários (β = 0,10). Para cada ponto percentual de aumento no indicador de exposição, houve aumento de 10% na taxa de hospitalização de idosos, 8% em internações de crianças, e 5% para a faixa etária intermediária, mesmo ajustando por IDH e número médio de hemogramas. Não foi encontrada associação entre AH% e a taxa de hospitalização por parto. CONCLUSÕES: O indicador de poluição atmosférica mostrou associação com a ocorrência de doenças respiratórias, em especial nos grupos etários mais vulneráveis da Amazônia brasileira, podendo ser utilizado na abordagem dos efeitos da queima das florestas na saúde humana.